Variasi Waktu Terhadap Penyerapan Merkuri (Hg) Oleh Eceng Gondok (Eichhornia crassipes) (Studikasus: Air Danau Bekas PETI di Jorong Jujutan, Nagari Lubuk Gadang, Kecamatan Sangir, Kabupaten Solok Selatan. - Fauzi Deswandri; Fadhillah Fadhillah (Departemen Teknik Pertambangan FT UNP, 2019)
Illegal gold mining occurred at Jorong Jujutan, Nagari Durian Tarung, Sangir District , South Solok Regency produce a puddle of water in the form of a small lake with Mercury (Hg) Level 0.0076 mg/L above the quality standards based on the rule of West Sumatera Gubenur No. 5 the year 2008 is 0.002 mg/L. This research is an experimental study where Eceng Gondok with a mass of 600 gr is placed on a container containing 2L of water with a Mercury rate of 0, 0076mg/L. The time variation observed is 3, 6, and 9 days. Based on the results of the study found 1 gram of Eceng Gondok is able to absorb Hg of 2.15 x 10-5 mg/L in 3 days is equivalent to 80 % of the Mercury content in the sampel. However, time variations of 3, 6, and 9 days had no significant effect on the absorption of Mercury (Hg) by Eceng Gondok (Eichornia crassipes). This result was evidenced by the test of Kruskal Wallis with the result (Hcount = 4.2738) < (Htable = 7.815). Then H0 is accepted meaning there is no significant influence of time variation on the absorption of Mercury (Hg) by Eceng Gondok. Keywords: Eceng Gondok, experimental, time variations, mercury absorption (Hg), Kruskal Wallis